Directional interactions between current and prior saccades - Jones, Stephanie A. H.; Cowper-Smith, Christopher D.; Westwood, David A. (Frontiers in Human Neuroscience, 2014)
One way to explore how prior sensory and motor events impact eye movements is to ask someone to look to targets located about a central point, returning gaze to the central point after each eye movement. Concerned about the contribution of this return to centre movement, Anderson et al. (2008) used a sequential saccade paradigm in which participants made a continuous series of saccades to peripheral targets that appeared to the left or right of the currently fixated location in a random sequence (the next eye movement began from the last target location). Examining the effects of previous saccades (n-x) on current saccade latency (n), they found that saccadic reaction times (RT) were reduced when the direction of the current saccade matched that of a preceding saccade (e.g. two left saccades), even when the two saccades in question were separated by multiple saccades in any direction. We examined if this pattern extends to conditions in which targets appear inside continuously marked locations that provide stable visual features (i.e. target ‘placeholders’) and when saccades are prompted by central arrows. Participants completed 3 conditions: peripheral targets (PT; continuous, sequential saccades to peripherally presented targets) without placeholders; PT with placeholders; and centrally presented arrows (CA; left or right pointing arrows at the currently fixated location instructing participants to saccade to the left or right). We found reduced saccadic RT when the immediately preceding saccade (n-1) was in the same (vs. opposite) direction in the PT without placeholders and CA conditions. This effect varied when considering the effect of the previous 2-5 (n-x) saccades on current saccade latency (n). The effects of previous eye movements on current saccade latency may be determined by multiple, time-varying mechanisms related to sensory (i.e., retinotopic location), motor (i.e., saccade direction), and environmental (i.e., persistent visual objects) factors.